Answer :

Answer:

r = va/(e - v)

Step-by-step explanation:

v = er/(r + a)

vr + va = er

va = er - vr

va = r(e - v)

r = va/(e - v)

Answer:

The answer is

[tex]r = - \frac{va}{v - e} [/tex]

Step-by-step explanation:

You have to get rid of fraction first :

[tex]v = \frac{er}{r + a} [/tex]

[tex]v(r + a) = er[/tex]

[tex]vr + va = er[/tex]

Next, you have to move all the r-variables to one side :

[tex]vr + va = er[/tex]

[tex]vr - er = - va[/tex]

Lastly, make r the subject :

[tex]vr - er = - va[/tex]

[tex]r(v - e) = - va[/tex]

[tex]r = - \frac{ va}{v - e} [/tex]

Other Questions